Technical and Economic Assessment of Technologies for Forage Land Improvement - A. V. Lavrov; A. Kh. Tekushev; S. A. Davydova (Сельскохозяйственные машины и технологии, 2024)
The paper highlights that the development of the forage base relies on crop cultivation technologies that ensure high productivity, meet the domestic market’s demand for high-quality feed, reduce labor costs and increase energy efficiency in feed preparation and storage. (Research purpose) The paper aims to conduct a comparative assessment of the technical and economic indicators of traditional, intensive, and high technologies, as well as machine complexes, for forage crop production. (Materials and methods) The study is based on scientific publications from 2011 to 2022 that focus on the improvement of natural lands for forage crop production, as well as on analytical and information materials, and other available sources. For a comprehensive technical and economic assessment of traditional, intensive and high-intensity technologies, as well as machine complexes used in forage crop production, the following indicators are selected: labor costs, fuel consumption, metal usage, and specific energy consumption. (Results and discussion) The study is conducted using the VIM methodology. A classifier of agricultural technologies is proposed to assess the technical and economic indicators of various types of agricultural machinery. The study results in the development of technological schemes for the reclamation of overgrown lands, the radical and surface improvement of herbage species composition and the radical improvement of herbage species composition in cultivated and natural forage lands. Additionally, the efficiency coefficient of energy consumption for the compared technologies across different soil and climatic zones are calculated. (Conclusions) A comparative analysis of the technical and economic indicators of machine complexes, including both traditional and advanced multifunctional systems, enables the recommendation of optimal solutions for forage production based on land productivity. The most resource-efficient option for producing a unit of output is achieved through the implementation of high technologies for improving forage lands.